Analisis Pengaruh Struktur Kepemilikan Manajerial, Kepemilikan Institusional, dan Kepemilikan Asing terhadap Kebijakan Dividen Perusahaan - Maulidiyah, Arista; Umaimah, Umaimah (CV. Lafadz Jaya, 2023)
This study aims to test the effect analysis of managerial ownership structure, institutional ownership, and foreign ownership as independent variables on dividend policy as the dependent variable. The data collection method used is a quantitative method. The population in this study are all corporate sectors listed on the Indonesia Stock Exchange (IDX) for the 2019 period with a total of 615 companies. The data is obtained by collecting the company's annual financial report data on the IDX web. This study used a purposive sampling technique and the samples used were 96 companies that fit the criteria. Testing was carried out using multiple regression analysis techniques. The regression results show that the structure of managerial ownership and institutional ownership has no effect on dividend policy. Meanwhile, foreign ownership has an effect on dividend policy with a significant level of 10%.